2022
DOI: 10.1111/jonm.13793
|View full text |Cite
|
Sign up to set email alerts
|

Association between spiritual care competency and perceived professional benefit among nurses: A cross‐sectional study

Abstract: Aims This study aimed to investigate the status quo of nurses' spiritual care competency and their relationship with perceived professional benefit. Background Spiritual care has always been considered a vitally important part of holistic nursing. Understanding the spiritual care competency of nurses during the COVID‐19 pandemic can help nursing managers understand the weak links in spiritual care practice and improve the quality of nursing service. As a positive emotional experience and cognitive evaluation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…Te SCC of intern nursing students in this study was higher than the pre-COVID-19 SCC of Chinese trainee nursing students [49] and Iranian nursing interns [50] and lower than that among Iranian nursing students during the same COVID-19 pandemic period [51]. Possible reasons for this include the following: (1) Te threat faced and the particular life-saving process involved during the pandemic facilitated the relationship between nursing staf and patients, patients had greater spiritual care needs, and nursing staf perceived patients' spiritual needs more easily [21]. Past literature [49] used a censored version of the Chinese version of the scale, and diferent authors have diferent interpretations and expressions of the Chinese version of the SCC scale.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Te SCC of intern nursing students in this study was higher than the pre-COVID-19 SCC of Chinese trainee nursing students [49] and Iranian nursing interns [50] and lower than that among Iranian nursing students during the same COVID-19 pandemic period [51]. Possible reasons for this include the following: (1) Te threat faced and the particular life-saving process involved during the pandemic facilitated the relationship between nursing staf and patients, patients had greater spiritual care needs, and nursing staf perceived patients' spiritual needs more easily [21]. Past literature [49] used a censored version of the Chinese version of the scale, and diferent authors have diferent interpretations and expressions of the Chinese version of the SCC scale.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, successfully implementing spiritual care with patients can help nurses feel that they do not have an ordinary job but rather a spiritual calling and even a "divine blessing," which will allow nurses to gain job satisfaction and maintain a positive attitude toward their work [20]. A previous study [21] also showed that nurses' spiritual care competence (SCC) had a positive correlation with perceived professional beneft; when SCC was stronger, nurses had more positive feelings and reported more satisfactory experiences. Nurses are the primary providers of spiritual care [22].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have explored factors that contribute to high-quality nursing care. Li et al (2022) found that spiritual care competence is positively associated with the perceived professional usefulness of nurses. Haldane et al (2022) highlight the challenges nurses faced during the COVID-19 pandemic, emphasizing the need for adequate support and resources to maintain high-quality care.…”
Section: Introductionmentioning
confidence: 97%
“…The healthcare system in Yemen has been severely affected by ongoing con ict, which has led to a decline in healthcare delivery and access to services (Dureab et al, 2020;Qirbi & Ismail, 2017). In addition to the many challenges that health care providers face in providing quality care (Dureab et al, 2020), understanding and improving health service quality is therefore crucial to ensuring that the limited resources available are used effectively and e ciently (Li et al, 2022). Given the limited research on nurses' perceptions of the quality of health services in Yemen, this study aims to ll this gap by using the SERVPERF scale to assess the quality of health services in the country.…”
Section: Introductionmentioning
confidence: 99%
“…"Spirituality" derives from the Latin word "spiritus" (being alive or life is supreme) and is an essential component of human well-being [30]. Tere is no uniform defnition of spirituality in China, but it is generally accepted that spirituality is a force that is intrinsically connected with the meaning of life [31].…”
Section: Introductionmentioning
confidence: 99%